A qualitative study on experience of nurses caring for patients with delirium in ICUs in China: Barriers, burdens and decision making dilemmas - Peng Yue; Ling Wang; Chang Liu; Ying Wu (Elsevier, 2015)
Purpose: The purpose was to explore the experiences of nurses caring for patients with delirium in ICU in China. Methods: Semi-structured qualitative interviews were conducted with 14 ICU nurses in Beijing, China. Audio recordings of the transcripts were coded and analysed thematically. Results: The emergent themes reflected clearly similar experiences and were titled as follows: Internal and external barriers to care; Care burden: workload, psychological pressure and injury; Dilemmas in decision-making: balancing risks and benefits. Conclusions: The results of this qualitative study have provided a rich description of the perceptions of a sample of nurses caring for patients with dementia in Beijing. Clearly, the nurses suffered from their work experiences in several aspects: they lacked the knowledge and skills required assessing and managing the patients as early as possible; they were physically and psychologically stressed while looking after the patients and faced with dilemmas and compromises in their decision-making.